(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Zinc oxide (ZnO) nanoparticles are widely employed in various industries due to their unique physicochemical properties; however, their increasing environmental and biological exposure has raised significant health concerns the scientific community as a whole is becoming more interested in nanotechnology. biomedical applications are just a few of the many uses for zinc oxide nanoparticles (ZnO NPs). The injection of ZnO nanoparticles in the present investigation increased serum MDA levels and decreased serum CAT levels relative to the control group.